2020
DOI: 10.5194/essd-12-1385-2020
|View full text |Cite
|
Sign up to set email alerts
|

Description of the multi-approach gravity field models from Swarm GPS data

Abstract: Abstract. Although the knowledge of the gravity of the Earth has improved considerably with CHAMP, GRACE, and GOCE (see appendices for a list of abbreviations) satellite missions, the geophysical community has identified the need for the continued monitoring of the time-variable component with the purpose of estimating the hydrological and glaciological yearly cycles and long-term trends. Currently, the GRACE-FO satellites are the sole dedicated provider of these data, while previously the GRACE mission fulfil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…The models published so far (GOCO01s, GOCO02s, GOCO03s, and GOCO05s) were used in a wide range of applications, for example, for global and local high-resolution models (e.g., Huang and Véronneau, 2013;Pail et al, 2016Pail et al, , 2018Klees et al, 2018;Slobbe et al, 2019), geophysical studies (e.g., Rummel et al, 2011a;Abrehdary et al, 2017;W. Chen et al, 2018), oceanographic studies (e.g., Farrell et al, 2012;Siegismund, 2013), or geodetic height unification (e.g., Vergos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The models published so far (GOCO01s, GOCO02s, GOCO03s, and GOCO05s) were used in a wide range of applications, for example, for global and local high-resolution models (e.g., Huang and Véronneau, 2013;Pail et al, 2016Pail et al, , 2018Klees et al, 2018;Slobbe et al, 2019), geophysical studies (e.g., Rummel et al, 2011a;Abrehdary et al, 2017;W. Chen et al, 2018), oceanographic studies (e.g., Farrell et al, 2012;Siegismund, 2013), or geodetic height unification (e.g., Vergos et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This one-year gap may be completed by gravity fields derived from the GNSS tracking of three Swarm satellites, in low-Earth orbit since 11/2013 [56,57]. Indeed, it was demonstrated that precise satellite positions from the geodetic-quality GNSS receivers (one receiver aboard each Swarm satellite) could be processed to produce monthly gravity fields that, although with a reduced spatial resolution of 1300 km and more noise, are able to produce reasonable estimates also for the mass trends in Greenland [58][59][60][61].…”
Section: Updated Estimate Of Mass Change In the Greenland Ice Sheet From Satellite Gravimetrymentioning
confidence: 99%
“…Many scholars have discussed the possibility of using the Swarm model to detect time variable gravity signals. The results indicate that the time variable gravity signals of Swarm model are mainly concentrated in the long wave part, and the Swarm model has the possibility of monitoring the regional TWSC [22][23][24][25]. Some scholars used the Swarm model to detect TWSC and droughts in the ARB [19,25,26], and the main purpose of their studies is to use the Swarm model to fill the gap between GRACE and GRACE-FO missions.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the time variable gravity signals of Swarm model are mainly concentrated in the long wave part, and the Swarm model has the possibility of monitoring the regional TWSC [22][23][24][25]. Some scholars used the Swarm model to detect TWSC and droughts in the ARB [19,25,26], and the main purpose of their studies is to use the Swarm model to fill the gap between GRACE and GRACE-FO missions. However, to best of our knowledge, there is no literature combining GRACE, GRACE-FO and Swarm models to construct a continuous long observations series to detect and characterize the regional droughts.…”
Section: Introductionmentioning
confidence: 99%